If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2senx + -1 + cosx = 0 Reorder the terms: -1 + cosx + 2ensx = 0 Solving -1 + cosx + 2ensx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '1' to each side of the equation. -1 + cosx + 1 + 2ensx = 0 + 1 Reorder the terms: -1 + 1 + cosx + 2ensx = 0 + 1 Combine like terms: -1 + 1 = 0 0 + cosx + 2ensx = 0 + 1 cosx + 2ensx = 0 + 1 Combine like terms: 0 + 1 = 1 cosx + 2ensx = 1 Add '-2ensx' to each side of the equation. cosx + 2ensx + -2ensx = 1 + -2ensx Combine like terms: 2ensx + -2ensx = 0 cosx + 0 = 1 + -2ensx cosx = 1 + -2ensx Divide each side by 'osx'. c = o-1s-1x-1 + -2eno-1 Simplifying c = o-1s-1x-1 + -2eno-1 Reorder the terms: c = -2eno-1 + o-1s-1x-1
| -5+p=9+3p | | 1/2(5x-8)=-9 | | 5m+4m=9 | | 15+15p=-9(-3p+13) | | -6h+5=-10-7h+9 | | -2(20h-18)-20h=3(-h-7) | | g=(x+7)(x+3) | | -12r+6(-16r-5)=-6(19r+19) | | 2(3x+4)=3(6x-5) | | 9+7j=4j | | X+5-2x=3+x | | x=2000000+0.333y | | 2x-24=82 | | -7-3n=-5n | | -7-2r=4+9r | | 2+4*5=30 | | -8=-3n+5n | | -6(-m-8)=-10m | | (2x-1)/3=(5x-6)/4 | | -10-7q=10-9q | | 11n-9=5n+45 | | 3(2r+14)=2(25+4) | | -9-9(13t-1)=6(-20t-10) | | 5n+22=22 | | 3(f-2)=7(f+2) | | C+5-2x=3+x | | -4y+b= | | 4(x+5)=-4x-20 | | 12n+22=5 | | 18d+18+20=2(15d-17) | | 5(x+1)-6x=-11x | | f(p)=p^2-6p+1 |